Decreased gastric tone and delayed gastric emptying precede neutrophil infiltration and mucosal lesion formation in indomethacin-induced gastric damage in rats - M.H.L.P. Souza; L.E.A. Troncon; F.Q. Cunha; R.B. Oliveira (Brazilian Journal of Medical and Biological Research, 2003)
Gastric antral dysmotility has been implicated in the pathogenesis of indomethacin-induced gastric damage, but the relationship between gastric motor abnormalities and mucosal lesions has not been extensively studied. We investigated whether changes in gastric tone and gastric retention correlate with mucosal lesions and neutrophil migration in indomethacin-induced gastric damage in rats. Indomethacin, either 5 or 20 mg/kg (INDO-5 and INDO-20), was instilled into the stomach, and then gastric damage, neutrophil migration, gastric tone and gastric retention were assessed 1 or 3 h later. Gastric damage was calculated as the sum of the lengths of all mucosal lesions, and neutrophil migration was measured by assaying myeloperoxidase activity. Gastric tone was determined by a plethysmometric method, and gastric retention of either saline or Sustacal® was evaluated by a scintigraphic method. Gastric damage was detectable 3 h after either INDO-5 or INDO-20, but not after 1 h. Neutrophil migration was significantly higher 3 h after INDO-20 as compared with INDO-5 or control group, but not after 1 h. Values of gastric tone 1 and 3 h after either INDO-5 (1 h = 1.73 ± 0.07 ml; 3 h = 1.87 ± 0.03 ml) or INDO-20 (1 h = 1.70 ± 0.02 ml; 3 h = 1.79 ± 0.03 ml) were significantly lower than in controls (1 h = 1.48 ± 0.05 ml; 3 h = 1.60 ± 0.06 ml). Gastric retention of saline was higher 1 h after INDO-5 (58.9 ± 3.3%) or INDO-20 (56.1 ± 3.1%) compared to control (45.5 ± 1.7%), but not after 3 h. There were no differences concerning gastric retention of Sustacal® between the various groups. Indomethacin induced decreased gastric tone and delayed gastric emptying, which precede mucosal lesion and neutrophil infiltration. These results indicate that there is no relationship between these gastric motor abnormalities and mucosal lesion in indomethacin-induced gastropathy.